Tuberculosis infection in patients with inflammatory bowel diseases. Clinacal cases - Maria U. Timanovskaia; Yuliya R. Shaykhtdinova; Elena U. Zhulina; Dmitrii S. Kulakov; Anna V. Kagramanova; Oleg V. Knyzev; Asfold I. Parfenov (Терапевтический архив, 2023)
In most cases Tuberculosis (TB) affects the lungs, but 10–15% of patients have extrapulmonary TB localisations, that is difficult to diagnose. TB is more spread among patients having the human immunodeficiency virus and among those who receive immunosuppressive therapy, specifically in patients with inflammatory bowel disease requiring long-term treatment with immunosuppressants and/or biologics. The symptoms of intestinal TB are nonspecific and may include chronic diarrhea, weight loss, fever and ascites. Differential diagnosis includes Crohn's disease, malignant neoplasms, periappendiceal abscesses, yersiniosis, etc. The article presents cases showing similarity of the intestinal form of TB with Crohn's disease, complexity dealing, diagnosing and treating patients with inflammatory bowel disease also having latent tuberculosis infection